Loneliness, belonging and psychosomatic complaints across late adolescence and young adulthood: a Swedish cohort study - Karina Grigorian; Viveca Östberg; Jonas Raninen; Sara Brolin Låftman (BMC, 2024)
Abstract Background Loneliness and belonging refer to social connectedness and are associated with young people's health; however, the relationship between these constructs and their impact on health is still being discussed. A dual continuum model of belonging and loneliness has been suggested, consisting of four groups depending on the state of loneliness and belonging: socially fulfilled (low loneliness, high belonging), socially indifferent (low loneliness, low belonging), socially searching (high loneliness, high belonging), and socially distressed (high loneliness, low belonging). The aim of this study is to examine loneliness and belonging in a Swedish sample of 17-18-years-olds who were followed over 3 years, and the associations that these aspects share with young people's psychosomatic complaints during these ages. Methods Swedish cohort data collected among late adolescents (age 17-18 in 2019) who were followed up in young adulthood (age 20-21 in 2022) (n = 2684) was used to examine the associations between loneliness, belonging, and psychosomatic complaints. Loneliness and belonging were measured by single items and the cross-combinations of these. Three psychosomatic complaints were assessed: stomach ache, headache, and difficulties falling asleep, and a summary index was calculated. Results Linear regression analyses showed that loneliness was positively and belonging was negatively cross-sectionally associated with psychosomatic complaints. The socially fulfilled group reported fewer psychosomatic complaints compared to all other groups, while the socially distressed group reported the highest level of psychosomatic complaints. Additional adjustment for sociodemographic characteristics barely affected the estimates. The prospective analysis supported these patterns; however, after adjustment for earlier psychosomatic complaints, the only statistically significant difference in subsequent psychosomatic complaints was found between the socially fulfilled and the socially distressed groups. Conclusions Loneliness and belonging (separately and the cross-combinations of these) were cross-sectionally associated with psychosomatic complaints in late adolescence and in young adulthood. Prospectively, only the most vulnerable group in the dual continuum model, the socially distressed group, experienced more psychosomatic complaints than the socially fulfilled group, indicating a temporal relationship. Knowledge about the more nuanced links may be useful for developing specific public health recommendations and interventions for youth, targeting the most vulnerable groups.